If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (48 + -2x)(62 + -2x) = 0 Multiply (48 + -2x) * (62 + -2x) (48(62 + -2x) + -2x * (62 + -2x)) = 0 ((62 * 48 + -2x * 48) + -2x * (62 + -2x)) = 0 ((2976 + -96x) + -2x * (62 + -2x)) = 0 (2976 + -96x + (62 * -2x + -2x * -2x)) = 0 (2976 + -96x + (-124x + 4x2)) = 0 Combine like terms: -96x + -124x = -220x (2976 + -220x + 4x2) = 0 Solving 2976 + -220x + 4x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(744 + -55x + x2) = 0 Factor a trinomial. 4((24 + -1x)(31 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(24 + -1x)' equal to zero and attempt to solve: Simplifying 24 + -1x = 0 Solving 24 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -1x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1x = 0 + -24 -1x = 0 + -24 Combine like terms: 0 + -24 = -24 -1x = -24 Divide each side by '-1'. x = 24 Simplifying x = 24Subproblem 2
Set the factor '(31 + -1x)' equal to zero and attempt to solve: Simplifying 31 + -1x = 0 Solving 31 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-31' to each side of the equation. 31 + -31 + -1x = 0 + -31 Combine like terms: 31 + -31 = 0 0 + -1x = 0 + -31 -1x = 0 + -31 Combine like terms: 0 + -31 = -31 -1x = -31 Divide each side by '-1'. x = 31 Simplifying x = 31Solution
x = {24, 31}
| v^-3/v^-6 | | -8x-6=-2x-60 | | -n=1/3^-5 | | (x^2-4x-2)x(x+7)= | | 3(2p+3q)+-4q= | | -7x-6=-12x-41 | | -n=1/4^-4 | | (x^2-4x-2)(x+7)= | | -n=1/9^-2 | | -14x+6=-6x+38 | | -14x+6=-6+38 | | 3x-2=-4x+33 | | 17x-2=8x+88 | | -n=1/5^-5 | | 9y-1=-10+12y | | -5(7n-4)+3= | | 2y-14=4y+4 | | P=2(26)+2(91) | | 5y+6y-81=7y+102+65 | | 3t^4=8t | | x+x+125000=550000000 | | 12x+8y-12=0 | | 4*x-9/2+12=0 | | 51x^2-5x-4= | | x+x+4=238 | | -(6y+5)-(-5y-7)=-5 | | 14-2x+39x-18x=256-60x-657x | | 13-42/7 | | 7+3p-4=9p+10-5p | | -x/3+58= | | -3b=-12 | | 2b+3(b-2)=4 |